ANALISIS STRATEGI PEMASARAN PRODUK DENGAN METODE MOORA - Gortap Lumbantoruan; Eva Julia Gunawati Harianja (Universitas Methodist Indonesia, 2020)
Multi - Objective Optimization On The Basis Of Ratio Analysis or often referred to as the MOORA method is a method that is often used as a method of decision making that uses optimization techniques to solve complex problems that have many criteria or multi-criteria. The MOORA method has the ability to separate various factors by separating the subjective part of the factors into several decision-making attributes by forming a decision matrix. The decision matrix will be normalized and optimized for each criterion to produce a preference value that can be used as a decision making. This method separates the criteria values ​​that have different characteristics, namely criteria with benefit characteristics (beneficial) from criteria with cost characteristics (not profitable). In this study, an analysis using the MOORA method was carried out on the right product marketing strategy based on various factors, both factors originating from internal and external factors with the aim of determining the strategy that the company will implement in marketing products so that the company has a competitive advantage for win the market from competitors. The results of the analysis show that the differentiation strategy has a higher preference value, namely 56.576497 and the cost leadership strategy with a value of 54.790304 and market segmentation strategies with a value of 53.206742.